Bande dessinée and the Penal Imaginary: Graphic Constructions of the Carceral Archipelago. Issue 2 (1st September 2019) - Forsdick, Charles
Abstract : The article offers an overview of the history and cultural representations in visual media from the 1860s onwards of French penal colonies or bagnes, and their status as graphic lieux de mémoire. It focuses specifically on French Guiana and New Caledonia and seeks to contextualise the portrayal of the motif in a varied corpus of bandes dessinées. The article argues that graphic history provides a unique forum in which aspects of the penal colonies about which there is little understanding – the transcolonial itineraries of convicts; the penal everyday; the role of carceral heritage as part of a useable past – are elucidated. Although some works primarily foreground celebrity bagnards such as Eugène Dieudonné or Henri Charrière (Papillon), albums such as those of Stéphane Blanco and Laurent Perrin allow the potential of the bande dessinée to create connections that are multilayered and multidirectional.